POTENCIAL DE MITIGAÇÃO DE CO2 DE MATERIAIS CIMENTÍCIOS NA FASE DE USO - John, Vanderley M.; Punhagui, Katia Regina Garcia; Quattrone, Marco; Reis, Daniel Costa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Due to the wide range of applications, the low cost, the easy-to-obtain raw materials and the easy-to-built 3D structures at ambient temperature, cementitious materials have been the most consumed construction materials. However, the cement production accounts for about 6-8% of anthropogenic CO2 emissions. Emission mitigation strategies of the cement industry have focused on the cement production phase and there are few proposals for reducing impacts during the in-use phase of cementitious materials. In this way, this work aims to estimate the CO2 mitigation potential associated with efficiency gains from the industrialization of Brazilian concretes and mortars market. For this purpose, the CO2 mitigation potential was assessed considering an increase of the fraction of industrialized products. Two scenarios were analysed. The reference scenario presents, "business as usual", the CO2 emissions of cement production as a function of its market share for concrete and mortar. The low-carbon scenario presents results obtained due to an increase of the use of industrialized cementitious products and a decrease of the clinker content in cement. Input data came directly from cement producers and sectorial organizations. Results indicate a significative CO2 mitigation potential 80Mt, approximately 5.1% of CO2 emissions due to the cement production from 2014 to 2050.